Morphology and surface ultrastructure of Dadaytrema oxycephala (Digenea: Cladorchiidae) with a new host record from Peruvian Amazon floodplain - Cuadros R.C. (2018)
The authors are grateful to Cienciactiva of CONCYTEC for the financial support provided to the Master Program in Aquaculture Health of the UPCH (Management Agreement N° 230-2015 FONDECYT).